(untitled) (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2013)
Three samples from the natural heavy concentration of the upper back sands at S.Torpes beach was analysed by microscopy, MEV and microprobe in order to characterize the mineralogical composition of the ore minerals. Because of the strong homogeneous granulometry the sand was only divided in two fractions, above and below the 125 micron sieve. Each fraction was subjected to magnetic separation by magnet hand and heavy liquid (bromoform). The paramagnetic fraction was subjected to Frantz electromagnet. Magnetic and paramagnetic fractions were studied in reflection microscopy, SEM and electronic microprobes. These techniques showed that the heavy fraction of these sands is composed on average by magnetite (71%), ilmenite (12%), hematite (8%) and mixed grains (9%). Textural aspects of the three main mineral compositions as well as its chemical composition and structural formula were further characterized. We also identified minor amounts of monazite and alteration minerals (rutile, psudorutile, ilmenorutile and titanite) and sulphides, all in very small amounts. It was possible to determine the mineralogical “average” composition of the sand combining the results of this study with the study of Pombo et al. (2006).